PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DENGAN MODEL COOPERATIVE TIPE THINK PAIR AND SHARE DI KELAS V SD SEMEN PADANG 1 - Arlini, Sri Mutia; Eliyasni, Rifda; Farida S, Farida S (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe researchis animed to improve the students’ learning outcomes in learning the Social Study Subject by using the Cooverative, Think Pair and Share Model at5th grade of SD Semen Padang 1. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were teachers (practitioners) and 21 students. The result of this research shows an excalation from cycle I to cycle II on :a) planning of 7.2%, b) implementation, teacher aspect and student aspects of 19,6%, and c) student learning outcomes of 8,7%. It can be concluded that used Cooperative Model Type Think Pairand  Share can improve students achievement in learning social study of elementary school. Keywords :  Learning outcomes, Social study, model